Business Strategies of the Multinational Corporations - Laura Diaconu (CES Working Papers, 2012)
The international strategic management facilitates the development of the international strategies that shape a large context for reaching the main goals of a multinational company. At a conceptual level, there are many similarities between designing a strategy that could be used only in one country and drawing up a strategy for a number of markets. Yet, it has to be mentioned that the development of an international strategy involves a more complex process than in the case of a national one. All these aspects, together with the determinants of the internationalization, will be largely argued in the present paper.
Keywords: F23; 330; multinational corporations; international strategies; business internationalization Romania